2017
DOI: 10.1080/16549716.2017.1362826
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a participatory multisectoral maternal and newborn intervention on birth preparedness and knowledge of maternal and newborn danger signs among women in Eastern Uganda: a quasi-experiment study

Abstract: Background: Knowledge of obstetric danger signs and adequate birth preparedness (BP) are critical for improving maternal services utilization. Objectives: This study assessed the effect of a participatory multi-sectoral maternal and newborn intervention on BP and knowledge of obstetric danger signs among women in Eastern Uganda. Methods: The Maternal and Neonatal Implementation for Equitable Systems (MANIFEST) study was implemented in three districts from 2013 to 2015 using a quasi-experimental pre–post compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…Another study in northern Nigeria reported significantly greater improvements in the intervention communities that received additional demand-side interventions, as about 22% of the women knew at least 4 maternal danger signs compared with 10% at baseline [39]. This finding also corroborates a participatory multi-sectoral intervention study in Uganda which reported that the intervention significantly increased the knowledge of at least three obstetric danger signs [40]. Other studies have shown that community-based intervention on BP/CR were effective in raising women's knowledge of danger signs [9,41,42].…”
Section: Knowledge Of Danger Signs and Birth Preparednesssupporting
confidence: 54%
“…Another study in northern Nigeria reported significantly greater improvements in the intervention communities that received additional demand-side interventions, as about 22% of the women knew at least 4 maternal danger signs compared with 10% at baseline [39]. This finding also corroborates a participatory multi-sectoral intervention study in Uganda which reported that the intervention significantly increased the knowledge of at least three obstetric danger signs [40]. Other studies have shown that community-based intervention on BP/CR were effective in raising women's knowledge of danger signs [9,41,42].…”
Section: Knowledge Of Danger Signs and Birth Preparednesssupporting
confidence: 54%
“…Another study in northern Nigeria reported significantly greater improvements in the intervention communities that received additional demand-side interventions, as about 22% of the women knew at least 4 maternal danger signs compared with 10% at baseline (39). This finding also corroborates a participatory multi-sectoral intervention study in Uganda which reported that the intervention significantly increased the knowledge of at least three obstetric danger signs (40). Other studies have shown that community-based intervention on BP/CR were effective in raising women's knowledge of danger signs (9,41,42).…”
Section: Knowledge Of Danger Signs and Birth Preparednesssupporting
confidence: 54%
“…In this supplement, we share a special issue of 10 different papers of which this paper is part. The rest of the nine papers share specific results [2532]. In addition to this design paper, there is one more methodological paper that describes the PAR approach in more detail [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this design paper, there is one more methodological paper that describes the PAR approach in more detail [33]. Two of the papers [25,26] summarize the results of the intervention on some of the key outcomes of the study (knowledge about maternal and newborn danger signs, birth preparedness and utilization of maternal and newborn health services and newborn care practices). Two other papers describe the characteristics of saving groups and the saving practices of the community for maternal and newborn health, highlighting opportunities for promoting saving for maternal and newborn health [27,28].…”
Section: Discussionmentioning
confidence: 99%